Impact of tides and winds on estuarine circulation in the Pearl River Estuary. (15th September 2018) - Lai, Wenfeng; Pan, Jiayi; Devlin, Adam T.
Abstract: The Finite-Volume Coastal Ocean Model (FVCOM) is used to simulate the dynamics of the circulation in the Pearl River Estuary (PRE), validated against the in-situ measurements of a cruise survey. The model simulation agrees well with observed sea level at local tide gauge stations and reproduces observed characteristics of the currents. A simplified model run without wind forcing reveals that there is a significant spring-neap variation in the along-estuary circulation. Additional sensitivity runs that include up-estuary and/or down-estuary winds are also implemented. These results reveal that the cross-estuary adjustment of stratification and mixing induced by along-estuary winds is stronger than the along-estuary wind straining effect; these yields enhanced stratification and weakened mixing under the up-estuary wind. During spring tide, the response of the along-estuary circulation to the along-estuary wind forcing is weak, while during neap tide, the up-estuary and down-estuary winds may induce substantial variations in the along-estuary circulation. The analysis on the momentum budget and turbulent stress reveals the different dynamic response of the estuarine circulation in the PRE to different wind forcing conditions, identifying a significant modification to estuarine circulation by the wind-tide interaction. Highlights: The high spatial resolution FVCOM model is run in the Pearl River Estuary region. The estuarine stratification can be affected by the cross-estuary adjustment in the PRE. The wind forcing can strongly adjust the longitudinal circulation in the neap tide. In the spring tide, the wind forcing has less influence on the longitudinal circulation.